PENGGUNAAN MEDIA RODA BACA PUTAR DALAM MENINGKATKAN KEMAMPUAN MEMBACA AWAL SISWA KELAS 1 SDN BATUPUTIH LAOK II - Dandy Kurniawan; Trio Wahyudi; Siti Subaida; Hemayatul Kubro; Zakiyah Zakiyah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research is motivated by the low level of early reading skills among several first-grade students at SDN Batuputih Laok II, where students still face difficulties in recognizing alphabet letters, frequently switch them, and some do not recognize letters at all. The purpose of this study is to describe the use of the